Use of research questionnaires in the NHS Bowel Cancer Screening Programme in England: impact on screening uptake. - Watson, J; Shaw, K; Macgregor, M; Smith, S; Halloran, S; Patnick, J; Beral, V; Green, J (Royal Society of Medicine Press Ltd, 2013)
BACKGROUND: The NHS Bowel Cancer Screening Programme in England offers biennial screening to those aged 60-74 using a faecal occult blood test (FOBt) sent by post. Data from this national clinical programme can also be used for research. Awareness of the impact of such studies on screening participation is important. AIMS: To investigate the effect on screening uptake of adding a research questionnaire to the postal screening invitation. METHODS: People invited for screening in 2008-10 in two areas of England were randomized to receive or not to receive an additional research study questionnaire, consent form and study information, either with their test kit or 2-3 days later. Uptake of screening was examined in relation to study mailings. RESULTS: Among 11,579 people invited for screening by the Midlands and North West Bowel Cancer Screening Hub, screening uptake was significantly lower in those who received study documents with their FOBt kit than in those who did not (48.6% vs 53.5% respectively: p < 0.001). The reduction in uptake was similar in men and women, and was greater in people living in more deprived areas. Among a further 36,195 people invited for screening by the Midlands and North West and Southern Hubs, sending study documents by separate mailing 2-3 days after the FOBt kit did not affect screening uptake (uptake with and without additional study mailing: Midlands and North West, 56.7% and 56.2% respectively, p = 0.6; Southern, 52.0% and 51.4% respectively, p = 0.5). CONCLUSIONS: Researchers planning studies that include contact with potential participants within the NHS Bowel Cancer and similar screening programmes should be aware of the potential impact on uptake.